Covalent organic polymer induces apoptosis of liver cancer cells via photodynamic and photothermal effects - Xu, Wenze; Zhang, Mengfan; Wang, Wenhui; Wang, Manzhou; Li, Bingjie; Li, Hao; Kuang, Donglin; Liang, Chao; Ren, Jianzhuang; Duan, Xuhua (Frontiers in Oncology, 2022)
The purpose of this study was to explore the photodynamic and photothermal effects of the supramolecular material Purp@COP and to test the anti-cancer effect on HepG2 cells in vitro. Materials and methods Purp@COP is a covalent organic polymer (COP) with robust tailoring heteroatom incorporation, plentiful pore structure, and multiple functions similar to the metal–organic framework (MOF). Hepatocellular carcinoma cell line HepG2 was cultured with Purp@COP for 24 h and treated with near-infrared 808-nm laser 1 W/cm2 for 10 min. Cell Counting Kit-8 (CCK-8) assay, colony formation assay, live–dead cell fluorescence staining, and Annexin V/propidium iodide (PI) staining flow cytometry were performed to detect the viability, proliferation, and apoptosis of the HepG2 cells. Results The supramolecular material Purp@COP exhibited significant photothermal performance under near-infrared 808-nm laser irradiation in vitro. With the treatment of Purp@COP and near-infrared 808-nm laser irradiation on HepG2 cells, cell viability and colony formation capacity were decreased, and the number and proportion of apoptotic cells were increased. Conclusions The supramolecular material Purp@COP has both photothermal and photodynamic effects and can significantly induce cancer cell death and inhibit the proliferation of cancer cells in vitro.